2013
DOI: 10.5194/angeo-31-1745-2013
|View full text |Cite
|
Sign up to set email alerts
|

Data-based modelling of the Earth's dynamic magnetosphere: a review

Abstract: Abstract. This paper reviews the main advances in the area of data-based modelling of the Earth's distant magnetic field achieved during the last two decades. The essence and the principal goal of the approach is to extract maximum information from available data, using physically realistic and flexible mathematical structures, parameterized by the most relevant and routinely accessible observables. Accordingly, the paper concentrates on three aspects of the modelling: (i) mathematical methods to develop a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 103 publications
3
121
0
Order By: Relevance
“…Our result of the substorm triggered by a solar wind dynamic pressure enhancement is consistent with the previous results of Petrinec and Russell (1996) and Shue and Kamide (1998) finding that solar wind density variations during periods of southward IMF can trigger substorms. Likewise, there is evidence for the triggering of tail reconnection by sudden enhancements in solar wind dynamic pressure (see, e.g., Milan et al (2007) and references therein).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result of the substorm triggered by a solar wind dynamic pressure enhancement is consistent with the previous results of Petrinec and Russell (1996) and Shue and Kamide (1998) finding that solar wind density variations during periods of southward IMF can trigger substorms. Likewise, there is evidence for the triggering of tail reconnection by sudden enhancements in solar wind dynamic pressure (see, e.g., Milan et al (2007) and references therein).…”
Section: Discussionsupporting
confidence: 93%
“…The second response is associated with slower processes such as magnetopause merging, plasma convection, particle losses due to pitch angle diffusion, charge exchange etc." (Tsyganenko, 2013). According to Lyons et al (2005), a P dyn enhancement under strongly southward interplanetary magnetic field (IMF) conditions "is found to cause both compressive auroral brightening away from the bulge region and a Harang-region substorm auroral brightening" -leading to a very broad auroral enhancement covering ∼ 10-15 h of MLT.…”
Section: P E Sandholt Et Al: the 25 July 2004 Interplanetary Cme Casementioning
confidence: 99%
“…Therefore, we cannot exclude that, in our case, the more intense and spread FAC effect overwhelms that of the temporally more localised B y leakage. Let us finally recall that some empirical magnetospheric models include the phenomenon of IMF penetration (Tsyganenko 2013). Concerning the relation of dH residuals and Sym-H index we have found that residuals seem to be strongly affected by the effect of the partial ring current in accordance with previous results (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The mainstream of models for the static part of B, due to the Tsyganenko algorithms T89, T96 and TS05 (see Tsyganenko, 2013, and references therein), follows a data-based approach towards correlation with parameters of geomagnetic activity like P dyn , the IMF vector B, the planetary index Kp and the disturbance storm-time index Dst (Rostoker, 1972). In T89, a physics-based description of the magnetospheric currents and the corresponding vector potential was introduced; the T96 model improved T89 in the description of the magnetopause geometry and the equatorial tail physics, whereas TS05 upgraded T96 with the inclusion of storm and substorm dynamics.…”
Section: Geomagnetic Fieldmentioning
confidence: 99%
“…An advantage of studying the individual particle motions is the physics insight gained, as well as the statistics built from ensembles of particles. In such models, the Lorentz equation of motion is solved, either in its full form or reduced in terms of the guiding-center approximation, and the driving forces are (as above) the dynamic magnetic field coming from the superposition of the Earth's terrestrial magnet with the fields generated by the magnetospheric current sources (Tsyganenko, 2013), and the electric field due to large-scale plasma convection and corotation with the Earth (Volland, 1973). An important factor, however, is the modeling of the electric field component induced by the time variation in the magnetic field.…”
Section: Introductionmentioning
confidence: 99%